If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2ln(-1) + -2ln(-2) = -1ln(4) Reorder the terms for easier multiplication: 2 * -1ln + -2ln(-2) = -1ln(4) Multiply 2 * -1 -2ln + -2ln(-2) = -1ln(4) Reorder the terms for easier multiplication: -2ln + -2 * -2ln = -1ln(4) Multiply -2 * -2 -2ln + 4ln = -1ln(4) Combine like terms: -2ln + 4ln = 2ln 2ln = -1ln(4) Reorder the terms for easier multiplication: 2ln = -1 * 4ln Multiply -1 * 4 2ln = -4ln Solving 2ln = -4ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '4ln' to each side of the equation. 2ln + 4ln = -4ln + 4ln Combine like terms: 2ln + 4ln = 6ln 6ln = -4ln + 4ln Combine like terms: -4ln + 4ln = 0 6ln = 0 Divide each side by '6'. ln = 0 Simplifying ln = 0 The solution to this equation could not be determined.
| 4b-3=16 | | 8z-z=30-9 | | 2ln(-1)-2ln(-2)= | | (x-(1+2i))(x+(1+2i))=0 | | X^4-13x^3+55x^2-81x+18=0 | | x+2=-6x+1 | | 2x-5x+6=12+2x-1 | | (3l+4)+(3-m)i=16-31 | | (-3)+2x=(-x)+6 | | 3x-11-2x=-3 | | X+6=3x-2(x-3) | | 4x-6=-x+54 | | y=2lx-2l+7 | | f-27=4f | | -3x=19-4 | | .10(x-4)+.02x=.06x-.7 | | -12=3x-5x | | 8t^2-19t+11=0 | | -6x-6=3x-15 | | y=sqrt-9-2 | | 209=19*11+13n | | 3y^3-193=0 | | 6-8n=0 | | (X-3)(x+4)-30=0 | | 8x-5-2x+5=18+8x | | -6x+3=-45+2x | | 5+24=x+8 | | 3(y-10)+1=6(y-8) | | -4x+8=-2+x | | 5-5z=-3z | | x+3=-26+15 | | -8.2-1.7= |